Passive maternal antibody transfer to eggs and larvae of tiger grouper (Epinephelus fuscoguttatus) - Nain Azman, M. H.; O., Rafidah; Ching, F. F.; Senoo, S.; Saad, Mohd Zamri (IOP Publishing, 2019)
The immune response of Tiger grouper (E. fuscoguttatus) broodstocks and its passive transfer of maternal antibodies to eggs and larvae were evaluated following vaccination with an inactivated V.harveyi. Tiger grouper broodstock (mean BW 8.66 ± 0.09 kg, n=19) were vaccinated intraperitoneally (IP) and followed by a booster two weeks post vaccination, while Controlled Non-vaccinated (CG) broodstock were IP injected with PBS. The serum antibody level against V.harveyi was monitored for two weeks on post-vaccination and monthly up to 5 months post-vaccination. This study showed that the Vaccinated Group (VG) broodstock induced significantly (P<0.05) higher in specific IgM antibody level against V.harveyi as compared to the CG, which in turn induced a marked increased (P<0.05) in specific IgM in eggs and larvae produced from VG broodstock at 14 weeks post vaccination. The findings from this study suggested that inactivated V.harveyi vaccines were able to stimulate the immune response in broodstock and passively transferred the maternal antibody to their eggs and larvae.